Attitudes Based Behaviours of Tadulako University Psycholinguistics Students in Learning English - Dr. Mawardin M. Said, M.Hum. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article deals with attitudes based behaviours of English education Psycholinguistics students in learning English. Their attitudes and behaviours are identified separatively then integratively. This scientific work is a result of research aimed at identifying attitudes dealing with like, dislike, and reason and behaviours dealing with practice, activities, and ways in learning English. Qualitative descriptive method was applied to have its data. Its subjects were 28 students of Psycholinguistics in English Education Study Program at Tadulako University. Its specific target is they have better behaviours which are appropriate with their attitudes in the foreign language.They have the skills since they are students of English language education. They can communicate ideas globally if they have skills of the global language. They have attitudes which have not been appropriate with their behaviours. Their attitudes have to be integrated with their behaviours appropriately to be professional human resources. The data indicate that the students’ Attitudes Based Behaviours in learning English are Consistent in Speaking since they mostly like and practice most Speaking and Unconsistent in Listening since they mostly dislike Listening but seldom practice Writing. Thereby, there is no problem in the consistent attitudes based behaviours but problem in the unconsistent ones.